Improving Environmental Care Characters Through E-Modules Based on Local Wisdom Mangrove Ecotourism - Syahrial Syahrial; Asrial Asrial; Dwi Agus Kurniawan; Nurul Delima Kiska (Jurnal Ilmiah Sekolah Dasar, 2021)
Teachers are less able to develop electronic modules that can improve student character. Electronic modules should be designed with materials that take advantage of the environment around students so that learning activities seem more real. This research was conducted to analyze the relationship between caring for the environment, integrated with an electronic module based on local wisdom of mangrove ecotourism. This type of research is quantitative associative. The sample in this study amounted to 22 people, using a sampling technique called purposive sampling. The data collection instrument used was a questionnaire. Data analysis used descriptive qualitative and quantitative statistics. The results in this study are that the environmental care character possessed by students has a good category, seen from the environmental care character indicator after using an electronic module based on local wisdom, strengthened by the correlation results obtained by 0.885 and produces a very good relationship, wherein using the electronic module has a close relationship with the character of caring for the environment. Therefore, both students and teachers need to implement electronic modules based on local wisdom that can be used to instil environmental care characters in students.